Background information on bean production in the fertile crescent zone of Uganda - Sengooba, T. (International Center for Tropical Agriculture, 1991)
The fertile crecent zone lies within the first 100 km of lake Victoria. It has medium to high fertility soils. The total annual rainfall is around 1000 mm with peak periods from March to June and from September to December. The area is classified as the robusta coffee/banana farming system zone. Beans are largely produced in association with other crops, with maize and bananas being the most important. Bean production in this zone is 14-17 percent of national production. Beans are used primarily for home consumption, but sales are common. Large to medium size grain types are preferred. The major production problems range from biotic and abiotic to social economical factors. (AS)